Waste Management in housing construction projects in Costa Rica: theory versus practice - Cruz-Zuñiga, Nidia (2023)
This article summarizes the results of several research projects that have been carried out at the School of Civil Engineering, under the author’s guidance, and framed in the research line of comprehensive waste management in construction. The objective of the research has been to generate information regarding the rate of waste generation in construction projects, at the moment only for housing projects, and to study their composition, in order to provide guidelines to national authorities for a possible regulation of the construction sector in terms of waste. One of the main hypotheses that have been studied is that there is a difference in the rate of generation of construction waste per square meter of construction depending on the type of construction used in the project. The methodology followed for these investigations has consisted of studying construction projects of various kinds during their gray work phase and quantifying all the waste that is produced on site, keeping track of weight and work progress. At the same time, characterizations by type of waste have been carried out in all cases, in order to show what type of construction material generates the greatest amount of waste, by weight and by volume. Additionally, the percentages of waste have been studied, carrying out a comparison between the amount of materials that enter each project and the waste that is reflected in the field, which was then compared with the percentages of waste that the theory indicates to estimate the budgets. Among the main conclusions reached by research to date are that waste is usually greater in practice than theory indicates, but that there are other variables involved in the generation of waste that make projects of the same type and even very similar to each other have very different generation rates. It has also been observed how projects built with modular systems do not precisely have lower waste generation rates, as indicated in theory. Additionally, it has been proven that construction projects that have more complex design elements tend to generate higher waste rates, which seems to be related to more elaborate architectural designs.